SURVEY OF MACROSCOPIC FUNGI FROM A FEW DISTRICTS OF TAMILNADU - S. SOOSAIRAJ; P. RAJA; A. KALA; P. KALAINGER RAJ (The Bioscan, 2012)
Macroscopic fungi were collected from a few localities in Tamilnadu to document their distribution and diversity. Gilled mushroom are short lived, abundant soon after the monsoon where as the Polyporus species could be collected for a prolonged periods. The present survey includes 26 species from different habitats. Maximum number of species were belong to the family Agaricaceae followed by Polyporaceae. The most common genera are Polyporus. Agaricus nivescens, Calocybe gambosa, Ganoderma lucidum, Geastrum fimbriatum, Lentinus tigrinus, Pleurotus ostreatus, Polyporus badius, Polyporus umbellatus, Schizophyllum commune and Panaeolus papilionaceus are edible. This is the preliminary survey of collection and identification of macroscopic fungi as this has not been done in this part of India. This study also envisages further study on the usefulness of these fungi in terms of their nutritive and medicinal values.